Possibilities and Tasks o f Landscape Planning in the frame ofSpatial Development - Schuchmann, Péter (4D Journal of Landscape Architecture and Garden Art, 2007)
Act XXI of 1996 named spatial planning and the spatial plan as the most important regulatory instrument for coordinating territorial processes. In the light of this legislation, the landscape planning profession is also looking for opportunities for landscape planning in connection with spatial planning.